2003
DOI: 10.1039/b212899c
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient epoxidation of cyclic alkenes catalyzed by ruthenium complex

Abstract: The epoxidation of cyclic alkenes with molecular oxygen was efficiently completed in excellent epoxide yield using a novel ruthenium complex as catalyst under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The result is consistent with those of Qi, Nam, and Ravikumar using ruthenium complex, cyclam or manganese acetate dihydrate as catalysts. [73][74][75][76] Iron, ruthenium and cobalt also showed excellent activity for cyclohexene epoxidation by molecular oxygen (Table 3). [77] Comparing the catalytic activities of different porphyrin catalysts, it was found that manganese porphyrin was the most effective since cyclohexene could be completely converted within 4.0 hours.…”
Section: Aldehydes As Reductantmentioning
confidence: 98%
“…The result is consistent with those of Qi, Nam, and Ravikumar using ruthenium complex, cyclam or manganese acetate dihydrate as catalysts. [73][74][75][76] Iron, ruthenium and cobalt also showed excellent activity for cyclohexene epoxidation by molecular oxygen (Table 3). [77] Comparing the catalytic activities of different porphyrin catalysts, it was found that manganese porphyrin was the most effective since cyclohexene could be completely converted within 4.0 hours.…”
Section: Aldehydes As Reductantmentioning
confidence: 98%
“…These include iodosylbenzenes, peroxyacids, hypochlorite, hydroperoxides, N-oxides, hydrogen peroxide, monoperoxyphthalate and potassium monopersulfate et al [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] However, the selective oxidation by green oxidants such as molecular oxygen or hydrogen peroxide is more attractive because of its cost-effectiveness and environmentally-friendly nature of the oxidant. [38][39][40][41][42] The chapter will try to cover the biomimetic homogeneous oxidation of organic compounds catalyzed by metalloporphyrins with green oxidants based on our group's research works, in which the oxidized substrates include alkanes, olefins, alcohols, aldehydes, sulfides etc. Both practical and mechanistic point of view for the homogeneous oxidations of different substrates catalyzed by metalloporphyrins will be presented.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: paguirre@ciq.uchile.cl; smoya@lauca.usach.cl alkenes. 20 Additionally ruthenium complexes containing the tetradentate square-planar ligand, 6,6 -bis(benzoylamino)-2,2 -bipyridine(H 2 BABP) have been employed as catalysts for oxygen-transfer reactions. 21 This paper presents a study of ruthenium complexes with polypyridyl ligands as catalysts for cyclohexene epoxidation.…”
Section: Introductionmentioning
confidence: 99%